2018
DOI: 10.1039/c8tc02598c
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of heterogeneous polymer layers in PEDOT:PSS films

Abstract: (3,4-Ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), a representative conducting polymer, is environment-friendly and offers easy processing and flexibility owing to its hydro-dispersive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…The shi of the peak at 1441 to 1430 cm À1 suggests that the PEDOT chain experienced a benzoid (coil)-to-quinoid (linear or expanded-coil) structural transition. [37][38][39][40] It can be conrmed that the initial polymerization rate is slowed and the PEDOT can be slowly polymerized linearly.…”
Section: Structure Of Pedot:pss Polymerized By Capmentioning
confidence: 99%
“…The shi of the peak at 1441 to 1430 cm À1 suggests that the PEDOT chain experienced a benzoid (coil)-to-quinoid (linear or expanded-coil) structural transition. [37][38][39][40] It can be conrmed that the initial polymerization rate is slowed and the PEDOT can be slowly polymerized linearly.…”
Section: Structure Of Pedot:pss Polymerized By Capmentioning
confidence: 99%
“…FT‐IR analysis demonstrated that PEGMA was well polymerized in P(SS‐ co ‐PEGMA) (Figure S3, Supporting Information) 18. Generally, CC skeletal vibration in the aromatic ring can be observed at 1640 cm −1 , and between 1410 and 1500 cm −1 .…”
Section: Resultsmentioning
confidence: 96%
“…The asymmetric stretching vibration of SO 3 can be observed between 1150 and 1250 cm −1 , whereas its symmetric stretching vibration can be observed between 1000 and 1050 cm −1 . The CO stretching vibration of PEGMA can be observed at 1730 cm −1 18. When the PEGMA molar ratio in P(SS‐ co ‐PEGMA) increases, there is an increase in the stretching vibration peak at 1730 cm −1 .…”
Section: Resultsmentioning
confidence: 97%
“…[13][14][15][16][17] PEDOT:PSS has been widely used polymer to fabricate organic TE thin lms so that various strategies have been developed to improve the TE parameterselectrical conductivity (s) and Seebeck coefficient (S). [18][19][20][21][22][23][24][25][26][27][28] Our group has developed PEDOT:PSS/PANI-CSA ML thin lms and observed enhanced TE properties compared to those of individual PEDOT:PSS or PANI-CSA layers. 5 The interdependency of the TE parameters of PEDOT:PSS thin lms was decoupled through growing alternating layers of PEDOT:PSS and PANI-CSA thin lms.…”
Section: Introductionmentioning
confidence: 99%